Determinants of combining budgetary innovations at the local level: experience from Slovakia (Public Sector Economics - submission site, 2022)
Slovakia belongs to a highly decentralised group of European countries, especially in terms of autonomy of local governments. The structure of local governments is extremely fragmented and therefore the individual capacities of many of them can be quite limited. Programme performance-based budgeting was introduced as a compulsory budgetary innovation for all larger local governments several years ago. Moreover, dozens of them have already experienced participatory budgeting. The aim of this article is to analyse the links between programme performance-based budgeting and participatory budgeting as local budgetary innovations and to identify the key political factors influencing the spread and durability of participatory budgeting in Slovakia. The findings show that in most municipalities there is a link between PB and PPBB, which is rather positive and could help to sustain PB in the municipality. The second part of the research reveals two political determinants influencing the success of participatory budgeting in Slovakia.